Status Tanah di Jalan Yosodipuro No. 138, Kelurahan Mangkubumen, Kecamatan Banjarsari, Kota Surakarta - Praninditya Estri Fauzia; Lego Karjoko (Faculty of Law Universitas Sebelas Maret Surakarta, 2021)
This study aims to answer how the land status should be on Yosodipuro Street No. 138, Mangkubumen, Surakarta from the perspective of agrarian law. This research uses prescriptive normative research, use a statutory approach and conceptual approach to answer the problem. The types and sources of research materials used are primary legal materials and secondary legal materials. The technique of collecting legal materials through literature study. The data analysis technique is the Logism deductive with interpretation method. From this study, it was found that the status of the land which should be based on the principle of Rechtsverwerking and the principle of trust and reasonable expectation, where the rights of the land should be given to the Plaintiff and can be registered as property rights.Penelitian ini bertujuan untuk menjawab bagaimana status tanah yang seharusnya di jalan Yosodipuro No. 138, Mangkubumen, Surakarta ditinjau dari perspektif hukum agraria. Penelitian ini merupakan penelitian normatif yang bersifat preskriptif, dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual untuk menjawab rumusan masalah. Teknik pengumpulan bahan hukum melalui studi kepustakaan. Teknik analisis data adalah silogisme deduktif dengan metode interpretasi. Dari penelitian ini diketahui bahwa status tanah yang seharusnya didasarkan pada asas Rechtsverwerking dan asas kepercayaan dan pengharapan yang wajar, dimana seharusnya tanah tersebut haknya diberikan kepada Pihak Penggugat dan dapat didaftarkan sebagai Hak milik.